Pendampingan Pekerjaan Semenisasi Jalan Tansijelelo Dusun II Desa Pulau Gadang Kecamatan XIII Koto Kampar - Putra, Agus Alisa; Adeswastoto, Hanantatur; Kaswara, Afdhal (Journal of Social and Community Service, 2022)
This community service activity aims to provide technical assistance in the cementing work of the Tansijelelo road in Dusun II, Pulau Gadang Village, XIII Koto Kampar District. The damaged and unsuitable road conditions are the main obstacles to community mobility and the transportation of agricultural products. In addition, limited community knowledge about road construction techniques and minimal available resources also exacerbate village infrastructure problems. Through a participatory approach, the community service team involved the community in the project implementation process, from planning, technical training, to field work. This activity not only resulted in physical improvements to road infrastructure, but also increased community capacity in understanding and implementing cement-based road construction. The results achieved showed an increase in accessibility, public awareness of the importance of good infrastructure, and active community involvement in maintaining development results. This assistance is expected to be a model for sustainable village infrastructure development and can be replicated in other areas with similar problems.